Screening of 50 microbial strains for production of ethanol and (R)-phenylacetylcarbinol - Julaluk Tangtua (2018)
The ethanol production capability of 50 microbial strains was determined under shaking condition. Yeast malt medium was used as carbon and complex nitrogen sources for conversion of reducing sugars into ethanol. In order to compare the capability of these wildtype micro-organisms which were readily available in Thailand for the production of ethanol and PAC, the corresponding carboligase activity of PDC of each microbial strain was determined. The level of ethanol production and ethanol yield in term of grams of ethanol produced per gram of sugar utilized being produced under the investigated condition could be ranked in the descending order as following; Candida shehatae 5843 (4.21 ± 0.39 g/l and 0.47 ± 0.05 g/g), C. maltosa 5165 (3.69 ± 0.25 g/l and 0.39 ± 0.03 g/g), C. lusitaniae 5156 (3.52 ± 0.19 g/l and 0.51 ± 0.03 g/g), and C. krusei 5624 (3.51 ± 0.04 g/l and 0.42 ± 0.00 g/g). Moreover, five microbial strains were identified in the microbial screening for PAC production: C. tropicalis 5350 (19.8 ± 3.36 mM), C. tropicalis 5144 (9.85 ± 1.42 mM), C. fennica 5618 (8.41 ± 0.95 mM), C. tropicalis 5306 (8.39 ± 0.69 mM), and C. utilis 5198 (8.29 ± 1.51 mM). Ranking of each microbial strain by taking into account the production level of dried biomass, ethanol, PAC, PDC, and remnant cells viability after cultivation resulted in two promising microbial candidates, namely, C. tropicalis 5350 and 5306 with corresponding score of 70.02% and 58.03%, respectively.